Efficacy of interventions to increase physical activity for people with heart failure: a meta-analysis - Paul Williams; Mark Haddad; Aliya Amirova; Theodora Fteropoulli (Open Heart)
Objectives This meta-analysis aims to (1) evaluate the efficacy of physical activity interventions in heart failure and (2) to identify intervention characteristics significantly associated with the interventions’ efficacy.Methods Randomised controlled trials reporting intervention effects on physical activity in heart failure were combined in a meta-analysis using a random-effect model. Exploratory meta-analysis was performed by specifying the general approach (eg, cardiac rehabilitation), strategies used (eg, action planning), setting (eg, centre based), mode of delivery (eg, face to face or online), facilitator (eg, nurse), contact time and behavioural change theory use as predictors in the random-effect model.Results Interventions (n=21) had a significant overall effect (SMD=0.54, 95% CI (0.13 to 0.95), p<0.0005). Combining an exercise programme with behavioural change intervention was found efficacious (SMD=1.26, 95% CI (0.26 to 2.26), p<0.05). Centre-based (SMD=0.98, 95% CI (0.35 to 1.62), and group-based (SMD=0.89, 95% CI (0.29 to 1.50),) delivery by a physiotherapist (SMD=0.84, 95% CI (0.03 to 1.65),) were significantly associated with efficacy. The following strategies were identified efficacious: prompts/cues (SMD=3.29, 95% CI (1.97 to 4.62)), credible source (standardised mean difference, SMD=2.08, 95% CI (0.95;3.22)), adding objects to the environment (SMD=1.47, 95% CI (0.41 to 2.53)), generalisation of the target behaviour SMD=1.32, 95% CI (0.22 to 2.41)), monitoring of behaviour by others without feedback (SMD=1.02, 95% CI (0.05 to 1.98)), self-monitoring of outcome(s) of behaviour (SMD=0.79, 95% CI (0.06 to 1.52), graded tasks (SMD=0.73, 95% CI (0.22 to 1.24)), behavioural practice/rehearsal (SMD=0.72, 95% CI (0.26 to 1.18)), action planning (SMD=0.62, 95% CI (0.03 to 1.21)) and goal setting (behaviour) (SMD=0.56, 95% CI (0.03 to 1.08)).Conclusion The meta-analysis suggests intervention characteristics that may be suitable for promoting physical activity in heart failure. There is moderate evidence in support of an exercise programme combined with a behavioural change intervention delivered by a physiotherapist in a group-based and centre-based settings.PROSPERO registeration CRD42015015280.